Paradigma Baru Hukum Pidana melalui Keadilan Restoratif: Tinjauan Konseptual, Praktik, dan Relevansinya di Indonesia - Brurry Hariyanto (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2026)
This study examines the emerging paradigm of criminal law through restorative justice (RJ) in Indonesia, highlighting its conceptual foundations, practical applications, and local relevance. Unlike traditional punitive or rehabilitative models, RJ emphasizes the restoration of social and moral relationships by requiring offenders to acknowledge wrongdoing, repair harm, and engage in dialogue with victims and communities. The research employs a qualitative approach, including field observations, interviews with mediators, offenders, victims, and community representatives, as well as document analysis of relevant laws and regulations. Findings indicate that restorative practices such as victim-offender mediation, community conferencing, and family group conferencing effectively reduce recidivism, increase victim satisfaction, and strengthen community cohesion. The study also identifies contextual challenges in Indonesia, including limited institutional capacity, inconsistent legal interpretation, and insufficient community and victim involvement. Theoretical implications affirm RJ as a relational and transformative model, not merely an alternative punitive measure. Practically, the findings support broader adoption of dialogical restorative processes, institutional support, and integration into rehabilitation programs to ensure sustainable social reintegration. This research contributes to understanding how global restorative justice principles can be culturally adapted in Indonesia, offering guidance for policy, judicial practice, and community-based interventions.